Mechanical and electrical properties of Cu-Steel bimetallic porous composite with a double-helix entangled structure. (1st January 2021) - Zhang, Wei; Xue, Xin; Bai, Hongbai
Highlights: A Cu-steel porous composite with double-helix entangled structure was developed. The mechanical and electrical properties of the porous composite were characterized. The effects of the copper/steel weight ratio on the performances were analyzed. The composite nonlinearity is related to the contact between internal wires. Abstract: Cu-steel bimetallic porous composite structures can be used as lightweight, damping, and electro-conductive elements in critical environments where traditional single materials become ineffective. In the present work, a novel Cu-steel bimetallic porous composite with a double-helix entangled structure was developed. The mechanical properties (static stiffness, loss factor, and tangent modulus) of the as-synthesized composite were characterized by compressive tests, and its electrical sensitivity to compressive force was examined by mechanical–electrical coupling tests. The effect of the copper/steel weight ratio on mechanical and electrical performances was analyzed in detail. It is found that the Cu-steel bimetallic porous composite with a relatively high weight ratio has a larger average loss factor and lower stiffness than that with a low weight ratio. The structural characteristics and complex microstructural changes of the deformed specimen allow the tangent modulus and stiffness to exhibit a non-proportional relationship with the weight ratio over a range of displacement. The resistance-force curves exhibit an obvious nonlinearity and degradation due to the contact between internal bimetallic wires. The resistance-stiffness history reveals that the mitigation of electrical conductivity continued with the enlargement of stiffness and weight ratio.